Em busca de uma gestão de qualidade: análise do componente de gestão de processos seletivos no portal de Coordenação Stricto Sensu do SIGAA da UFPB - Quirino, Sinval Gleryston Maciel (2019)
This research investigated the use of SIGAA in the administrative procedures of the stricto sensu selective processes of the Graduate Programs of the Federal University of Paraíba, seeking to identify the difficulties and solutions adopted by the coordinators when using information technology. Its overall objective was to analyze the level of efficiency and end-user satisfaction with the SIGAA selective process management module. To achieve this goal, a survey was conducted with the Program’s organization secretaries who operate the system through questionnaires, document review, expert consultation and the various tools of the SIGAA selective process management module, interviews and participant observation. It is a research of qualitative, descriptive and applied approach. From a qualitative analysis of the answers, it was noticed that the system does not have the necessary modules for process management, leading users to search for other software to complete the tasks. Furthermore, it was verified that there was no training and community involvement in the implementation of SIG-UFPB. These situations characterize a lack of IT Governance and an intermediate level of maturity. Thus, the research points to the need to adopt good practices in IT Governance at the institution level and complements in the system so it can be more efficient and effective as an administrative tool.